Decoupling Re-Analysis of CO2 Emissions and Economic Growth From Two Dimensions - Han, Yuling; Liu, Yiping; Liu, Xiao (Frontiers in Energy Research, 2022)
The 21st Conference of the Parties (COP 21) was a significant attempt by governments to make and monitor commitments to limit global warming. However, COP 23 “sought to continue the global momentum to decouple output from greenhouse gas (GHG) emissions.” Among the GHGs, carbon dioxide (CO2) is the major one most countries worry about. This paper examines the decoupling situations of China’s CO2 emissions and economic growth, considering the country’s progress situation from the year 2000 to 2019. For this, we employed two models: the environmental Kuznets curve (EKC) model for exploring the long-run decoupling status and the influence factors of CO2 emissions and the Tapio model for the short-run decoupling status. Later, the Tapio model was extended to analyze the influence of industrial structure, energy structure, and population structure. The long-term results suggest that China’s CO2 emissions have not decoupled yet, but the emission’s intensity has decoupled in mid-2006. The short-term decoupling results revealed that the degree of decoupling changed to weak from strong in the last five years. According to the influencing structure’s results, the industrial and energy structures inhibited CO2 emissions, but their influence was not strong enough to offset the impact of economic growth; however, the population structure indorsed CO2 emissions. Lastly, we found an unusual verdict that is the change of EKC into a U-shape from an inverted U-shape, and the observed reason is the control variable introduction. We also observed that the turning point became greater after introducing the industrial structure separately. Overall, from the perspective of the observed decoupling trends, it is suggested that China should strengthen and further optimize its energy structure to match the industrial structure.